An observational study of learning effects of peer-assisted learning tests in COVID-19 pandemic times - Holfert, Jonathan; Kesting, Marco Rainer; Buchbender, Mayte (Journal of Dental Education, 2021)
Purpose This study aimed to determine whether peer-assisted learning (PAL) is a more effective learning and test method in terms of oral- and maxillofacial surgery. Material and methods In July 2020, a total of 267 students took a PAL-based exam on fictional patients with surgical issues, in which they had to evaluate two fellow students and were themselves evaluated by two fellow students. The students evaluated their experience with the PAL-based exam through a questionnaire which consisted of five given statements (answer possibilities: agree, disagree, neutral) and two questions (answer possibilities: better, equal, worse) to rate. Results In the survey, 77.9% of the students rated PAL as a better learning method and 21% rated it as at least equally effective to the known multiple-choice (MC) test. A total of 74.9% of the students indicated that they learned more content with PAL and 20.2% said they learned the same amount; 83.7% said that their "clinical thinking has improved" through PAL. In the comments, 73% of the students noted that they think PAL is a good learning method, and at least 22% rated it as useful but in need of improvements. Only 5% did not see PAL as an acceptable learning method. In contrast to this, 1.3% saw PAL as a "bad alternative to MC tests." Conclusion PAL, especially peer assessment, might represent a better learning method as it might encourage students to deal more intensively with the learning content and to improve clinical thinking.
CRIS-Team WoS Importer:2021-10-01